A new index for extracting built-up land features using Landsat satellite imagery - Jellouli Amine; Chakouri Mohcine; El Hachimi Jaouad; Hajaj Soufiane; Jari Abdessamad; Adiri Zakaria (E3S Web of Conferences)
Land features mapping in urban regions are changing rapidly over time as a result of continuous urbanization. Spatial remote sensing allows continuous monitoring of this change using multi-date image data and providing a synoptic view. In light of this, a new spectral index based on pre-existing indices is suggested for the purpose of extracting built-up features in the Beni Mellal study area utilizing two Landsat-5 TM and Landsat-8 OLI images from 2013 and 2023. This time range of ten years enables the spatial and temporal monitoring of built-up surfaces. The accuracy of the results obtained is confirmed by using Pearson's correlation to land surface temperature and the two spectral indices, the Normalized Difference Moisture Index (NDMI) and Normalized Difference Vegetation Index (NDVI).